Cultural Resilience in the Digital Age: Artistic Interventions as a Response to Cognitive Warfare and Social Polarization - Marsili, M. (XIX Polish Sociological Congress, 2025)
In an era marked by deep societal uncertainty, fueled by digital transformations, armed conflicts, and post-pandemic trauma, cultural interventions emerge as crucial mechanisms for fostering resilience and social cohesion (Beck, 1992; Castells, 2012). The contemporary information ecosystem, shaped by social media and AI-driven content, exacerbates polarization, misinformation, and distrust in institutions, contributing to a collective sense of insecurity (Bennett & Livingston, 2018; Helbing, 2013). This phenomenon aligns with the logic of cognitive warfare, where adversarial actors exploit vulnerabilities in public perception to destabilize societies (Marsili, 2023; Hung & Hung, 2022). Marsili and Wróblewska-Jachna (2024) further highlight that the digital revolution and artificial intelligence have profoundly altered information systems, comparable to the advent of movable type printing, thereby reshaping social structures and interactions. This paper explores how artistic interventions—ranging from community-based art initiatives to immersive digital experiences—can act as countermeasures to cognitive manipulation and social fragmentation. By fostering critical engagement, cultural participation serves not only as a tool for well-being but also as a strategic response to contemporary hybrid threats (Inglehart, 2018; Norris & Inglehart, 2019). Drawing on interdisciplinary research in security studies, cognitive warfare, and digital humanities, this study examines case studies where artistic practices have been leveraged to rebuild trust, strengthen social capital, and promote adaptive capacities in uncertain times (Putnam, 2000; Florida, 2019). By analyzing initiatives in urban spaces, digital platforms, and institutional programs, the paper argues that culture should not merely be seen as a therapeutic tool but as an active component of societal resilience (UNESCO, 2021). In an age of information warfare and polycrises, artistic interventions represent a form of soft power, enabling communities to reclaim agency over their narratives and foster a renewed sense of belonging (Nye, 2004). The discussion will contribute to broader debates on culture as a strategic asset in contemporary social adaptation policies.